Evolution of carbon nanostructure during pyrolysis of homogeneous chitosan-cellulose composite fibers. (15th November 2021) - Zahra, Hilda; Sawada, Daisuke; Kumagai, Shogo; Ogawa, Yu; Johansson, Leena-Sisko; Ge, Yanling; Guizani, Chamseddine; Yoshioka, Toshiaki; Hummel, Michael
Abstract: Chitosan-cellulose composite fibers spun using a Lyocell technology are characterized by a homogeneous distribution and a close packing of the two biopolymers inside the fibrous matrix. Due to the intimate contact of cellulose and chitosan, synergistic effects can be observed during the pyrolysis of the composite fibers. In this study, the catalytic role of chitosan in altering the cellulose pyrolysis pathway in the composite fibers at moderate treatment temperatures up to 900 °C is confirmed. Analyses of the evolved gases during pyrolysis revealed that chitosan promoted cellulose dehydration and substantially decreased the formation of levoglucosan, explaining the higher char yield. The enhanced dehydration reaction is associated with the formation of intermolecular crosslinks due to the incorporation of nitrogen from chitosan in the resulting carbon structures. Nitrogen could also contribute to the in-plane disorder in the aromatic clusters when the pyrolysis is carried out at 500–700 °C, although the in-plane disorder is less noticeable from 700 to 900 °C. Nevertheless, the size of the aromatic cluster continues to grow when the composite fibers are pyrolyzed in a temperature range of 500–900 °C. Graphical abstract: Image 1